Cardiovascular disease in the World Trade Center Health Program General Responder Cohort. Issue 2 (14th December 2020) - Sloan, Nancy L.; Shapiro, Moshe Z.; Sabra, Ahmad; Dasaro, Christopher R.; Crane, Michael A.; Harrison, Denise J.; Luft, Benjamin J.; Moline, Jacqueline M.; Udasin, Iris G.; Todd, Andrew C.; Teitelbaum, Susan L.
Abstract: Background: Over 90, 000 rescue and recovery responders to the September 2001 World Trade Center (WTC) attacks were exposed to toxic materials that can impair cardiac function and increase cardiovascular disease (CVD) risk. We examined WTC‐related exposures association with annual and cumulative CVD incidence and risk over 17 years in the WTC Health Program (HP) General Responder Cohort (GRC). Methods: Post 9/11 first occurrence of CVD was assessed in 37, 725 responders from self‐reported physician diagnosis of, or current treatment for, coronary artery disease, myocardial infarction, stroke and/or congestive heart failure from WTCHP GRC monitoring visits. Kaplan–Meier estimates of CVD incidence used the generalized Wilcoxon test statistic to account for censored data. Cox proportional hazards regression analyses estimated the CVD hazard ratio associated with 9/11/2001 arrival in responders with and without dust cloud exposure, compared with arrival on or after 9/12/2001. Additional analyses adjusted for comorbidities. Results: To date, 6.3% reported new CVD. In covariate‐adjusted analyses, men's CVD 9/11/2001 arrival risks were 1.40 (95% confidence interval [CI] = 1.26, 1.56) and 1.43 (95% CI = 1.29, 1.58) and women's were 2.16 (95% CI = 1.49, 3.11) and 1.59 (95% CI = 1.11, 2.27) with and without dust cloud exposure, respectively. Protective service employment on 9/11 had higher CVD risk. Conclusions: WTCHP GRC members with 9/11/2001 exposures had substantially higher CVD risk than those initiating work afterward, consistent with observations among WTC‐exposed New York City firefighters. Women's risk was greater than that of men's. GRC‐elevated CVD risk may also be occurring at a younger age than in the general population.